The Use of Induced Pluripotent Stem Cells as a Model for Developmental Eye Disorders - Eintracht, Jonathan; Toms, Maria; Moosajee, Mariya (Frontiers in Cellular Neuroscience, 2020)
Approximately one-third of childhood blindness is attributed to developmental eye disorders, of which 80% have a genetic cause. Eye morphogenesis is tightly regulated by a highly conserved network of transcription factors when disrupted by genetic mutations can result in severe ocular malformation. Human-induced pluripotent stem cells (hiPSCs) are an attractive tool to study early eye development as they are more physiologically relevant than animal models, can be patient-specific and their use does not elicit the ethical concerns associated with human embryonic stem cells. The generation of self-organizing hiPSC-derived optic cups is a major advancement to understanding mechanisms of ocular development and disease. Their development in vitro has been found to mirror that of the human eye and these early organoids have been used to effectively model microphthalmia caused by a VSX2 variant. hiPSC-derived optic cups, retina, and cornea organoids are powerful tools for future modeling of disease phenotypes and will enable a greater understanding of the pathophysiology of many other developmental eye disorders. These models will also provide an effective platform for identifying molecular therapeutic targets and for future clinical applications.